The Effect of Love of Money, Perception of Entrepreneurial Opportunities, and Entrepreneurial Knowledge on Entrepreneurial Interest with Family Support as a Moderating Variable (International Journal of Economics and Management Research, 2026)
Entrepreneurial interest does not emerge instantly but develops through a gradual process that varies across individuals. This study aims to analyze the effect of love of money, perceived entrepreneurial opportunities, and entrepreneurial knowledge on entrepreneurial interest, with family support as a moderating variable. The research was conducted at Udayana University with a sample of 167 students, selected using a sample size calculator. Data were collected through a survey approach using questionnaires as the research instrument. The collected data were analyzed using path analysis. The results indicate that: (1) love of money has a significant effect on entrepreneurial interest; (2) perception of entrepreneurial opportunities significantly affect entrepreneurial interest; (3) entrepreneurial knowledge has a significant effect on entrepreneurial interest; and (4) perception of entrepreneurial opportunities moderated by family support significantly influence entrepreneurial interest. These findings imply that the entrepreneurial interest of Udayana University students is influenced by love of money, perceived entrepreneurial opportunities strengthened by family support, and entrepreneurial knowledge. The study reinforces empirical evidence on entrepreneurial interest and highlights the practical importance of enhancing financial motivation, opportunity recognition ability, entrepreneurial knowledge, as well as family and university support in fostering students’ entrepreneurial interest.